Eksplorasi Tafsir Digital: Studi Komparatif atas tafsir.web.id dan tafsirq.com - Lailatul Azizah, Siti Nur; Saidah, Saidah; Ismi, Fitrotul; Raihan, M. Alif; Maghfuri, Nabil; Abdillah, Asyhad (Canonia Religia, 2024)
The Industrial Revolution 4.0 era marks the beginning of the integration of technology in various aspects of human life, including in the study of the interpretation of the Qur’an. One of the manifestations is the emergence of various digital-based Qur'an interpretation products. This phenomenon is interesting to study, especially from a scientific point of view. Two sites that stand out in presenting digital interpretation products are tafsir.web.id and tafsirq.com. These two sites offer a variety of features and interpretations sourced from print interpretations of classical, medieval, and modern-contemporary scholarly works. This article analyzes the similarities and differences between the two interpretation products through a comparative study approach. The research questions asked include: What are the reference sources used by the tafsir.web.id and tafsirq.com sites? And what are the advantages and disadvantages of the features offered by these two sites? The research results show: First, tafsir.web.id refers to Tafsir Kalām al-Mannān, Tafsir Jalālain, Tafsir Anwārul Hilālain fī Ta'qubāt 'alā Jalālain, and Tafsir Ibn Kathīr, while tafsirq.com only refers to the DSN MUI fatwa. Second, the advantages and disadvantages of the two sites complement each other; for example, features such as digital Al-Qur'an mushafi, ulama fatwas, daily prayers, and wisdom stories are available on tafsir.web.id, but not on tafsirq.com. However, neither do not yet provide a feature to guide the knowledge of tajwid and murattal Al-Qur'an. Hopefully, this article can be a reference for the public to get to know online tafsir and a source for studying the Qur’an and other Islamic sciences.